A assembleia de classe como prática possibilitadora da vivência democrática: uma experiência com alunos do Ensino Fundamental 2 - Mantovani, Claudia Kampus (2017)
The practice of the class assembly is an opportunity to live the democratic life, involving the transformation of interpersonal relations. Through the dialogue, all participants have the opportunity to express their opinion on conflicts or issues of interest to the group, finding solutions to problems and enabling reflective thinking about actions and reactions of everyday events. This research focus on analyzing the practice of class assembly in Elementary School 2 of a private school, as well as the conception, importance, characteristics, fundamentals and benefits of this experience for the democratic process, having as main references Michael Apple , Josep Puig, Ulisses Araújo, Telma Vinha and Jean Piaget. The research had a qualitative approach and the instrument used was the semistructured interview, where it was analyzed the practice of the class assembly in Elementary School 2, in a private school in the west zone of the capital of the State of São Paulo, being explored the benefits of the assembly looking for reflecting on the real possibility of the assembly bring together the school and the democratic experience. From the analysis of the interviews, it was concluded that the assembly made it possible to regulate interpersonal relations within the school environment and, in some cases, outside school's cases, as well as the in-school democratic experience, although the assembly in 2016 did not have been performed with the frequency proposed by Araújo and Puig